Is science neurotic? - Maxwell, Nicholas, 1937- (Imperial College Press, 2004)
Is Science Neurotic? sets out to show that science suffers from a damaging but rarely noticed methodological disease -- ""rationalistic neurosis."" Assumptions concerning metaphysics, human value and politics, implicit in the aims of science, are repressed, and the malaise has spread to affect the whole academic enterprise, with the potential for extraordinarily damaging long-term consequences.